2021
DOI: 10.1002/etc.5166
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation in Mercury, δ15N, and δ13C Among 3 Adélie Penguin (Pygoscelis adeliae) Populations in the Northern Antarctic Peninsula Region

Abstract: Mercury (Hg) is a pervasive environmental contaminant that accumulates in the organs and tissues of seabirds at concentrations capable of causing acute or long-term adverse health effects. In the present study, Hg concentrations in Adélie penguin (Pygoscelis adeliae) egg membranes and chick feathers served as a proxy for Hg bioavailability in the marine environment surrounding the northern Antarctic Peninsula. Stable isotopes were measured in conjunction with Hg to infer information regarding feeding habits (δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…An alternative explanation for this, is that skua diet changes according to the phenology and peaks in availability of their prey, and opportunistic changes in consumption of penguin eggs and chicks across the season according to their availability occurs (Graña Grilli et al 2014;Ibañez et al 2022). The increase in δ 15 N values would indicate that with the advance of the season, skuas shift from feeding on penguin eggs to chicks, as the latter display higher levels of Hg (McKenzie et al 2021). RBC δ 13 C values indicated that in both seasons brown skuas had fed on Antarctic prey during the early incubation and pre-laying period.…”
Section: Trophic Ecology As a Driver Of Blood Thgmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative explanation for this, is that skua diet changes according to the phenology and peaks in availability of their prey, and opportunistic changes in consumption of penguin eggs and chicks across the season according to their availability occurs (Graña Grilli et al 2014;Ibañez et al 2022). The increase in δ 15 N values would indicate that with the advance of the season, skuas shift from feeding on penguin eggs to chicks, as the latter display higher levels of Hg (McKenzie et al 2021). RBC δ 13 C values indicated that in both seasons brown skuas had fed on Antarctic prey during the early incubation and pre-laying period.…”
Section: Trophic Ecology As a Driver Of Blood Thgmentioning
confidence: 99%
“…Once assimilated, MeHg bioaccumulates within marine organisms and biomagnifies through marine food webs (Bargagli 2008;Driscoll et al 2013). Long-lived, upper trophic level predators, such as many Antarctic seabirds, are therefore potentially exposed to high Hg concentrations through their prey (Bearhop et al 2000;Bargagli 2008;Tavares et al 2013;Mills et al 2020;McKenzie et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation